Cloud‐resolving model intercomparison of an MC3E squall line case: Part I—Convective updrafts. Issue 17 (6th September 2017) - Fan, Jiwen; Han, Bin; Varble, Adam; Morrison, Hugh; North, Kirk; Kollias, Pavlos; Chen, Baojun; Dong, Xiquan; Giangrande, Scott E.; Khain, Alexander; Lin, Yun; Mansell, Edward; et al.
Abstract: An intercomparison study of a midlatitude mesoscale squall line is performed using the Weather Research and Forecasting (WRF) model at 1 km horizontal grid spacing with eight different cloud microphysics schemes to investigate processes that contribute to the large variability in simulated cloud and precipitation properties. All simulations tend to produce a wider area of high radar reflectivity ( Z e  > 45 dBZ) than observed but a much narrower stratiform area. The magnitude of the virtual potential temperature drop associated with the gust front passage is similar in simulations and observations, while the pressure rise and peak wind speed are smaller than observed, possibly suggesting that simulated cold pools are shallower than observed. Most of the microphysics schemes overestimate vertical velocity and Z e in convective updrafts as compared with observational retrievals. Simulated precipitation rates and updraft velocities have significant variability across the eight schemes, even in this strongly dynamically driven system. Differences in simulated updraft velocity correlate well with differences in simulated buoyancy and low‐level vertical perturbation pressure gradient, which appears related to cold pool intensity that is controlled by the evaporation rate. Simulations with stronger updrafts have a more optimal convective state, with stronger cold pools, ambient low‐level vertical wind shear, and rear‐inflow jets. Updraft velocity variability between schemes is mainly controlled by differences in simulated ice‐related processes, which impact the overall latent heating rate, whereas surface rainfall variability increases in no‐ice simulations mainly because of scheme differences in collision‐coalescence parameterizations. Key Points: Majority of the schemes overestimate convective updraft speed and radar reflectivity aloft Spread in updraft velocity is consistent with spreads in both cold pool intensity and latent heating Updraft velocity variability between microphysics schemes is largely attributed to ice‐related parameterizations